Ventricular arrhythmias and prognosis of patients after explantation of an infected ICD compared to patients with newly diagnosed heart failure using the wearable cardioverter-defibrillator. (19th May 2022) - Mueller-Leisse, J; Brunn, J; Zormpas, C; Hohmann, S; Hillmann, HAK; Eiringhaus, J; Bauersachs, J; Veltmann, C; Duncker, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The wearable cardioverter-defibrillator (WCD) is a tool for temporary protection from sudden cardiac death (SCD). It is used in patients with newly diagnosed heart failure with reduced ejection fraction (HFrEF) as well as in patients with a preexisting ICD indication who need explantation of the device. There is no data on long-term prognosis after the WCD in this latter group of patients. Methods: All patients receiving the WCD at a Medical School between 2012 and 2017 were analyzed. Patients with newly diagnosed HFrEF from the PROLONG-II study were compared to patients receiving the WCD after an ICD explantation. Follow-up (FU) data were analyzed after 3 months and at last available FU including WCD data, clinical status, medication, echocardiography and ECG. Results: 353 patients (69% male) with newly diagnosed HFrEF from the PROLONG-II study were compared to 29 patients (86% male) having received a WCD after explantation of an ICD (45% with secondary preventive indication). Mean baseline LVEF was 25±8% and 34±13% respectively (p<0.001). Follow-up was 2.8±1.5 and 3.2±1.8 years. WCD shocks occurred in 14 (4%) of the patients with newly diagnosed HFrEF and in 3 (10%) patients after ICD explantation (2 with a secondary preventive indication). During long-term FU, patients with an explanted ICD had a poorer prognosis compared to patients with newly diagnosed HFrEF (p=0.02), and appropriate WCD shocks were associated with even higher mortality in patients after ICD explantation (p=0.045). Conclusion: Patients after ICD explantation have an increased risk of ventricular arrhythmias and WCD shocks, but also show an increased risk of all-cause mortality despite wearing the WCD compared to patients with newly diagnosed HFrEF.